2008
DOI: 10.1021/jf800255c
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Functional Properties of Amylose Complexes with Genistein

Abstract: Complexes of amylose or high-amylose corn starch (HACS) with genistein were prepared by the acidification of an alkali solution to yield a V 6IotaIotaIota structure. The amylose-genistein complexes exhibited significantly higher genistein content (11 mg/100 mg of complex) than HACS-genistein complexes (9 mg/100 mg of complex). The effect of genistein on the amylose complexes was examined in different genistein-amylose ratios, and a model for genistein organization in the amylose complexes was suggested. The co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
83
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(88 citation statements)
references
References 35 publications
5
83
0
Order By: Relevance
“…(23,24,151) Amylose complexes with lipids are not available to mouth and gastric digestion but become available under pancreatic conditions to release the included molecule. (85,152) This potential application has been demonstrated in vitro f o r s t e a r i c a c i d a n d polyunsaturated fatty acids (PUFA) (24) . Nanoencapsulation of CLA was demonstrated by Lalush et al (23) and patent application made based on complexes produced by the 36 continuous homogenization method.…”
Section: Encapsulation Of Flavor and Bioactive Substancesmentioning
confidence: 99%
“…(23,24,151) Amylose complexes with lipids are not available to mouth and gastric digestion but become available under pancreatic conditions to release the included molecule. (85,152) This potential application has been demonstrated in vitro f o r s t e a r i c a c i d a n d polyunsaturated fatty acids (PUFA) (24) . Nanoencapsulation of CLA was demonstrated by Lalush et al (23) and patent application made based on complexes produced by the 36 continuous homogenization method.…”
Section: Encapsulation Of Flavor and Bioactive Substancesmentioning
confidence: 99%
“…The ability of some phytochemicals to provide health benefits makes these compounds attractive to consumers (Cohen, Orlova, Kovalev, Ungar & Shimoni, 2008), resulting in an increased interest in bioactive compounds in foods (Shimoni, 2009). For example, phytosterols, found in fruits and vegetables, are well known to reduce low density lipoprotein-cholesterol levels lowering the risk of cardiovascular diseases (Moreau & Hicks, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Even though the formation of amylose inclusion complexes with a wide variety of molecules has been known for many years, only recently, have these inclusion complexes been seriously investigated as a delivery system of non-drug bioactive compounds (Cohen et al, 2008;Lalush, Bar, Zakaria, Eichler & Shimoni, 2005;Lesmes, Barchechath & Shimoni, 2008;Lesmes, Cohen, Shener & Shimoni, 2009;Zabar, Lesmes, Katz, Shimoni & Bianco-Peled, 2009), including conjugated linoleic acid (Lalush et al, 2005;Yang, Gu & Zhang, 2009) and genistein (Cohen et al, 2008). These investigations suggested that inclusion complexes can protect these compounds during their passage through the stomach, and be released in the small intestine by the action of enzymes on the amylose complexes (Lalush et al, 2005;Yang et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…All of these characteristics drive researchers to extensively study the amylose-inclusion complexes using different encapsulation methods (as discussed by Helbert and Chanzy [7], Yang et al [8], Putaux et al [9,10], and Ades et al [11]). In particular, many researchers defined different concepts of encapsulation efficiency of amyloseflavor complexes using the identical detection method (as discussed by Wulff et al [12], Itthisoponkul et al [13], Cohen et al [14], and Ades et al [11]). …”
Section: Introductionmentioning
confidence: 99%